2006
DOI: 10.1021/jp056246d
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Controlled Crystallization of Zinc Oxide Hexagonal Nanorings and Disks

Abstract: In this study, we have developed a novel route to the synthesis of ZnO nanorings, disks, and diskoidlike crystals on a large scale by a facile solution-based method by using polymers as crystal growth modifiers. The crystals precipitated with polyacrylamide (PAM) as the additive show ringlike morphology. A possible growth mechanism of the ZnO nanostructures based on typical polymer-crystals interactions in a mild aqueous solution is given. The polymer contains in the side chain a large number of amide ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
230
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(245 citation statements)
references
References 41 publications
12
230
2
1
Order By: Relevance
“…Arya et al [15] demonstrated that ZnO crystals exhibit different biosensor properties corresponding to their shape changes. Up to now, many different ZnO micro and nanostructures have been reported [16][17][18][19][20][21]. However, developing a facile, environment-friendly method to synthesize ZnO crystals with well defined complex morphology is still a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Arya et al [15] demonstrated that ZnO crystals exhibit different biosensor properties corresponding to their shape changes. Up to now, many different ZnO micro and nanostructures have been reported [16][17][18][19][20][21]. However, developing a facile, environment-friendly method to synthesize ZnO crystals with well defined complex morphology is still a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…88 Several works of ours have been conducted to pursue the morphology evolution and to clarify a complex problem derived from the metamorphic features in the morphology of ZnO during soaking in aqueous solutions. 85,109,121 The studies have shown that both specific solution chemistry and treatment parameters such as temperature, time, and pH have effects on the growth by selective promotion or prohibition of some characteristically crystalline planes. 85,109,121 With a solution containing hexamethylenetetramine and ammonia, the solution pH can be controlled by releasing OH À from the decomposition of hexamethylenetetramine during incubation.…”
Section: Morphological Evolution In Solutionmentioning
confidence: 99%
“…Actually, thin films of ZnO have a great deal of interest for applications as photovoltaic cells. 20) Furthermore, the formation of organic-inorganic hybrid films is impossible due to the steric hindrance of the PAM blocks.…”
Section: Zno Nanorods Grown From the Seeds On A Substratementioning
confidence: 99%